2005
DOI: 10.1007/s00106-004-1101-5
|View full text |Cite
|
Sign up to set email alerts
|

Markerlose Registrierung der Patientenlage

Abstract: Laser-scan registration of the auricle reduces logistics in image-guided lateral skull base surgery. The problem of temporary deformation of the auricle during CT imaging might be solved by an appropriate opening in the head support at the level of the auricles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The present authors have previously demonstrated the feasibility of a technique of mechanical surface registration: a stereolithographic negative of a bone surface is produced using the image data. Similar to a key in a keyhole, this negative can only be attached to the bone surface in one particular position, thus inherently performing the registration 114,125,126,127 . In optical surface registration, the surface information is gathered using contact-free optical systems.…”
Section: Surface Registrationmentioning
confidence: 99%
“…The present authors have previously demonstrated the feasibility of a technique of mechanical surface registration: a stereolithographic negative of a bone surface is produced using the image data. Similar to a key in a keyhole, this negative can only be attached to the bone surface in one particular position, thus inherently performing the registration 114,125,126,127 . In optical surface registration, the surface information is gathered using contact-free optical systems.…”
Section: Surface Registrationmentioning
confidence: 99%
“…3). The navigation software computes the target registration error (Fitzpatrick and West, 2001;Marmulla et al, 2005b) as the square root of the sum of squared deviation in all three spatial directions is ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi…”
Section: Referencing and Navigationmentioning
confidence: 99%
“…Registration techniques can be categorized into two main groups: (I) marker-based registration (Altobelli et al, 1993;Hassfeld et al, 1995;Howard et al, 1995;Schramm et al, 1999;Luebbers, 2004) and (II) markerfree registration (Troitzsch et al, 2003;Marmulla et al, 2004bMarmulla et al, , 2005bHoffmann et al, 2005). Marker-based registration requires markers that are apparent in the pre-operative images and are easily detectable on the patient during the procedure.…”
Section: Introductionmentioning
confidence: 98%
“…The existing intraoperative registration methods are either marker-based registration or marker-free registration (Luebbers et al, 2008;Zheng et al, 2007). The marker-based registration (Marmulla et al, 2005;Schramm et al, 1999) calculates the transformation parameters using the coordinates of some special additional markers (e.g. metal balls).…”
Section: Introductionmentioning
confidence: 99%